An obesity paradox in preterm birth: A case control study - Krystal Hunter; Michael Ehrlich; Jocelyn Mitchell-Williams (PLoS ONE, 2025)
The March of Dimes Global action report indicated that preterm birth (PTB) rates are increasing in most countries. It is the most important cause of neonatal deaths and the second leading cause of death in children under age 5. Literature reporting the relationship between maternal pre-pregnancy body mass index (BMI) and PTB has previously yielded inconsistent conclusions. Our objective is to fill in the knowledge gap by evaluating the interaction of socio-economic status (SES) and BMI and its relationship to the rate of PTB. This is a case control study using the Natality Data of the National Vital Statistics System from the years 2020–2022. BMI was a significant factor in PTB for lower socioeconomic status (LSES) women. For every increase in BMI, there was a decrease in the probability of PTB (OR = 0.923, 95% CI 0.915–0.931, P < 0.001). Those who were LSES also had a curved relationship with PTB indicating that the as BMI increases, the odds of PTB decreases up until a BMI value, then the PTB rate increases. This relationship was not found in higher economic status women. Our study had two significant findings. We first found an obesity paradox in PTB for those mothers who are LSES. We also found that the relationship between BMI and PTB was not linear but curvilinear, bridging the gap in the conclusions of other studies. This study fills in the knowledge gap of BMI and PTB by adding the consideration of social class and by creating a polynomial BMI term.